Criminological Review of Juvenile Perpetrators of Motor Vehicle Theft (Case Study of Palu Police Headquarters) - Pratama, Ignasius Caesar Rendy; Utami, Fidyah Faramita; Hasnawati (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This study aims to analyze the criminological factors underlying juvenile involvement in motorcycle theft crimes within the jurisdiction of the Palu City Police. The increasing participation of minors in criminal activities has become a serious concern as it contradicts the mandate of the Child Protection Law and the principles of restorative justice in the juvenile criminal justice system. This research employs an empirical legal method with a qualitative approach, conducted through interviews with law enforcement officers as well as document and literature studies. The findings reveal that the main factors driving juveniles to commit motorcycle theft include low family economic conditions, lack of parental supervision, unfavorable social environments, and peer influence. In addition, educational background and limited understanding of legal consequences further increase the likelihood of juvenile delinquency. Based on data from the Palu City Police during the 2023–2025 period, there were 1,680 reported motorcycle theft cases, with only one case resolved, one of which involved a minor perpetrator. These findings indicate the low effectiveness of law enforcement and child protection efforts at the local level. This study recommends strengthening the roles of families, schools, and communities in juvenile guidance and reinforcing the implementation of restorative justice to ensure fair legal protection for children in conflict with the law.